Agroecological Performance and Dietary Diversity Dataset: Household-Level Insights Using the TAPE (Tool for Agroecology Performance Evaluation) Framework and Qualitative 24hr Dietary Recall in Vihiga, Kenya (2023) - Clotuche, Emeline; Aluso, Lillian Olimba; Wanyama, Rosina Nanjala; Termote, Celine; Akingbemisilu, Tosin Harold (2025)
This dataset originates from a study conducted in September 2023 to assess agroecological performance and dietary diversity among farming households in Kenya. The research employed the Tool for Agroecology Performance Evaluation (TAPE) - 2022 VERSION, developed by the Food and Agriculture Organization (FAO), alongside a qualitative 24-hour dietary recall designed by the Alliance of Bioversity International and CIAT. The study aimed to characterize agroecological transitions, analyze farm-level biodiversity, and understand household food consumption patterns. The dataset includes information on 239 households, selected using stratified random sampling from 14 sub-locations across five sub-counties. Households were eligible if they had at least one woman aged 15–49 years. The data collection tools captured: i) Agroecological practices across ten dimensions. ii) Dietary diversity and nutritional intake. The principal investigators sought to answer key research questions, including: i) To what extent are households transitioning toward agroecological farming systems? ii) How does agroecological performance correlate with dietary diversity and nutrition? iii) What factors influence household food choices, preparation, and consumption? iv) How do different farming practices impact household resilience and sustainability? This dataset provides qualitative and quantitative insights into the links between agroecology, nutrition, and food security, offering a valuable resource for researchers, policymakers, and development practitioners.